Pelatihan dan Pendampingan Penggunaan Ejaan Bahasa Indonesia dalam Tayangan Teks Liturgi Ibadah di Jemaat GKI Diaspora Kotaraja Dalam Jayapura - Mawene, Aleda; Mokay, Meggy Merlin (Abdimas Indonesian Journal, 2024)
The representation of the function of language in the field of religion and spirituality is marked by the use of Indonesian in various forms of church services. This also applies to the GKI in Tanah Papua, especially in the service (diakonia) of the GKI church in Tanah Papua which is known as the Tri Vocations of the Church, namely fellowship, witness and service. All service activities require Indonesian as an effective and meaningful communication tool. One of them is the use of correct Indonesian spelling in the presentation of praise song texts by the Church's Media Team. The target for this training and mentoring is the GKI Diaspora Multimedia Team in Kotaraja Dalam. The initial survey (interview on Wednesday, 26 July 2023) with the GKI Diaspora Multimedia Team Kotaraja- Dalam showed that the team's activities in editing the text of the songs were not based on the applicable General Guidelines for Indonesian Spelling (PUEBI). Training activities were held on Monday, July 31 2023, at the GKI Diaspora Multi-Purpose Building, Kotaraja Dalam. Implementation time is 16.00—18.00 WIT. The activity was attended by 8 participants. Apart from that, mentoring was also carried out for 4 days via telephone communication, starting from 31 July to 3 August 2023. In the mentoring activity, training participants were challenged to edit spelling errors and writing word combinations in the Congregational Songbook of 300 song texts. The results of the observations showed that the participants were serious enough to improve. Within one week, 20 texts of the Congregational Song Songs were returned which had been edited and within 1 month the edited results of 300 Congregation Song Song texts were obtained. The text editing completion rate is considered successful. The completion rate for text editing in the first week of August 2023 reached 6.7% with the training participants' level of understanding of the material being (60%) in the sufficient category. There was a significant increase in performance and understanding in the 4th week of August by 100% with very good criteria. Thus, it is concluded that training and mentoring techniques can improve the GKI Diaspora Kotaraja Multimedia Team's proficiency in writing capital letters, punctuation marks and word combinations in accordance with the General Guidelines for Indonesian Spelling.service issues undertaken / researched. Abstracts include reasons for the selection of topics or the importance of research topics / community service, methods of research / devotion and outcome summary. The abstract should end with a comment about the importance of the result or a brief conclusion.